Breaking the language of design: semioclastics in the world of industrial design. Issue 3 (1st October 2016) - Ventura, Jonathan; Shvo, Galit
Abstract : Among Roland Barthes' theoretical universe, a central concept tends to be ignored – what Barthes defined as semioclastics This term echoes with the famous historical iconoclasm, i.e. the deconstruction of a symbol or a semiotic system. In this article, we claim that semioclastics can be applied as an inherent part of the design toolkit and for understanding design processes. Although the presence of function makes the possibility of a total deconstruction of the original symbol difficult, we would like to reveal the spectrum of interpretations of the term and the way it expands the limits of design. Taking under consideration that design will always refer to questions of usability, we wish to portray the changes in attitude towards the product and its sign, while looking through a "semioclastics filter."